ECONOMIC EFFICIENCY OF BREEDING TSIGAI SHEEP IN THE CENTRAL AND SOUTH – EAST EUROPE - Lana, Nastić; Ivanović, Sanjin; Marković, Todor (Economics of Agriculture, 2020)
Tsigai is an indigenous sheep breed present in entire Central and South-East Europe. Due to its low meat and milk production number of Tsigai sheep is in a sharp decline. But, there is a strong need to preserve valuable genetic resources of this breed. Therefore, the goal of this research is to evaluate economic performance of Tsigai breeding and to define strategies for its future use. In the paper profitability of Tsigai breeding is determined as well as economic efficiency of investments in Tsigai farms (using Net Present Value and Internal Rate of Return). To perform the analysis in risky circumstances authors applied sensitivity and decision tree approach. The results indicated that breeding of Tsigai sheep requires state subsidies to be profitable and economically efficient. Decision tree approach resulted in calclation of expected NPV. Investments in Tsigai farms proved to be economically efficient, but associated with high level of risk.